Towards an Educational Simulator to Support the CPU Scheduling Algorithm Education - Paschoal, Leo Natan; Biazotto, Joao Paulo; Spengler, Ana C. F.; de Oliveira, Myke Morais; Felizardo, Katia; Nakagawa, Elisa Yumi (2019 International Symposium on Computers in Education (SIIE), 2019)
Computer science students are introduced to different CPU scheduling algorithms. These algorithms are essential for understanding the functionalities of an operating system. However, the abstract nature of these algorithms makes it difficult to understand. To increase student achievement, some educational solutions have been developed (e.g., simulators). Despite that, these solutions have some limitations; for example, some of them only focus on algorithms for a specific type of system and others do not allow access, use, modifications or redistributions by third parties. This paper presents a new educational simulator that has been established to be available under the public domain and with an open license. The main characteristics of the simulator are described and a feasibility study on the simulator as a mechanism to support teaching is reported.